Environmental dimensions of antibiotic resistance: assessment of basic science gaps. Issue 12 (2nd October 2018) - Smalla, Kornelia; Cook, Kimberly; Djordjevic, Steven P; Klümper, Uli; Gillings, Michael
ABSTRACT: Antibiotic resistance is one of the major problems facing medical practice in the 21st century. Historical approaches to managing antibiotic resistance have often focused on individual patients, specific pathogens and particular resistance phenotypes. However, it is increasingly recognized that antibiotic resistance is a complex ecological and evolutionary problem. As such, understanding the dynamics of antibiotic resistance requires integration of data on the diverse mobile genetic elements often associated with antibiotic resistance genes, and their dissemination by various mechanisms of horizontal gene transfer between bacterial cells and environments. Most important is understanding the fate and effects of antibiotics at sub-inhibitory concentrations, and co-selection. This opinion paper identifies key knowledge gaps in our understanding of resistance phenomena, and outlines research needs that should be addressed to help us manage resistance into the future. Abstract : Key knowledge gaps in our understanding of antibiotic resistance phenomena are identified and research needs that should be addressed to help us manage resistance in the future are proposed